2022
DOI: 10.3390/vaccines10050773
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of COVID-19 Vaccine Mandates in Hawaii

Abstract: Having been affected by the highest increase in COVID-19 cases since the start of the pandemic, Honolulu and Maui counties in Hawaii implemented vaccine passport mandates for select industries in September 2021. However, the degree to which such mandates impacted COVID-19 mitigation efforts and economics remains poorly understood. Herein, we describe the effects of these mandates on changes in three areas using difference-in-difference regression models: (1) business foot traffic; (2) number of COVID-19 cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Vaccine mandates are effective at increasing vaccination rates, both for COVID-19 [259,260] and influenza vaccines [10,261] though studies on the impact of COVID-19 vaccine mandates are limited at this time. Among HCWs, one study of radiology departments with a site-specific mandate noted an improved vaccination rate as the institutional deadline approached [262].…”
Section: Towards the Futurementioning
confidence: 99%
“…Vaccine mandates are effective at increasing vaccination rates, both for COVID-19 [259,260] and influenza vaccines [10,261] though studies on the impact of COVID-19 vaccine mandates are limited at this time. Among HCWs, one study of radiology departments with a site-specific mandate noted an improved vaccination rate as the institutional deadline approached [262].…”
Section: Towards the Futurementioning
confidence: 99%
“…Overall, vaccine mandate announcements were followed by an increase in COVID-19 vaccine uptake in certain Canadian provinces. Studies in Canada and other countries have also demonstrated the positive effect of mandatory vaccination certificates on population vaccination rates [12] , [13] , [14] , [15] , [31] . We observed a significant impact of vaccine mandates in BC, AB, SK, MB, NS, and NL up to 10 weeks after vaccine mandate announcements.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the USA have shown that employment mandates are generally more accepted in the population and are more likely to address vaccination hesitancy compared government mandates [37] , [38] . Additionally, a study in Hawaii showed that business mandates were associated with an 8 % increase in vaccination rates among employers [39] . Given that we did not account for these factors, our findings may overestimate the impact of provincial vaccine mandate announcements on vaccination coverage or vaccine uptake in regions where municipal and/or employment mandates were implemented during or around the same time as the studied vaccine mandate announcements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These metrics have been vetted and used by the NIH RADx-UP initiative via a consortium of over 100 participating sites throughout the country [12]. Survey data were collected from March to August 2021, after COVID-19 vaccines were widely available for adults and before state mandates for vaccination were issued [13]. As summarized in Tables 1 and 2, the proportion of racial/ethnic groups among the total of 1124 adult respondents of this survey was representative of the community population based on US 2020 Census data as well as their vaccination status at the time of the study (Zipcode: 96792).…”
Section: Recruitment Strategymentioning
confidence: 99%